Impact of green management on CEO compensation: interplay of the agency theory and institutional theory perspectives - Goktan, A. Banu (Journal of Business Economics and Management, 2014)
There has been growing interest in green management practices among practitioners, researchers and regulators in recent years. However, there is limited research that examines the connection between natural environments and human resource management practices. The current study examined the relationship between Chief Executive Officer (CEO) compensation and green management practices within the agency theory and institutional theory frameworks. Results revealed a significant negative relationship between green management practices and CEO base pay, however, there was not a significant relationship between green management practices and CEO bonuses. In line with previous agency theory research, findings suggest a negative relationship between state regulation and CEO compensation in green states. An important implication for practice is that the negative relationship may strengthen negative perceptions about green management practices among CEOs and reduce willingness to implement green management practices.